Géohistoire des crues de l'Oubangui et problématique des inondations fluviales à Bangui, République Centrafricaine - Cyriaque-Rufin Nguimalet (Physio-Géo)
This work presents the risings' history of the Ubangi river at Bangui since 1889 and their impacts on people and goods in the urbanized floodplain. A documentary and interviewees and ground surveys data analysis allowed precisely floods dates and the evolutive stakes into the Ubangi river floodplain, regarding to the 1999 and 2019's phenomena (daily Q max of 12180 and 12400 m3.s-1 respectively). A statistical treatment of discharges data (annual mean and daily mean flows) over the 1911-2015 period helped to characterize risings between wet, average and dry periods. Major peak discharges considered are ones high or equal to 12000 m3.s-1. Eleven are observed in Bangui. According to GUMBEL distribution, the weakest frequency is at 6,5 years (Q = 12000 m3.s-1 in 1969) and the highest equals to 53 years (Q = 16000 m3.s-1 in 1916). The Qj-max of 12900 m3.s-1 for the year 1969 is close to the decennial value (12200 to 12880 m3.s-1). Other frequencies reach 22 years, for a daily Q max of 14400 m3.s-1 (in 1961). For the 1916 flood, the GEV, WEIBULL and Normal distributions give return times of 700 years for the first and more than 1000 years for both other. The risk levels were spatialized for three floods (1916, 1961 and 1999), which opens up possibilities for improving flood risk management, which is still very basic, as in Bangui as in the country as a whole.